Recent advances in mutagenesis for commercial fruit crop improvement: A comprehensive review - Sundarrajan, R V; Ravindran, C; Thangamuniyandi, M; Sankar, C; Prabhu, T; Anitha, T; Sathish, G; Gnanasekaran, M; Saraswathy, S; Rajangam, J (Plant Science Today, 2025)
Mutagenesis, the deliberate induction of genetic alterations, plays a critical role in modern fruit crop improvement. This review explores the impact of mutagenesis methods discussed on diverse fruit crops, highlighting advancements in traits. Such as developing dwarf fruit mutant lines with enhanced resistance to biotic and abiotic stressors, seedlessness, yield and fruit quality have been a major focus recently. Traditional breeding techniques have often led to a genetic bottleneck, limiting. diversity available for crop improvement. To overcome these limitations, plant breeders have adopted innovative approaches like genome editing and mutation. The mutagenesis experiments aim for a 30-80 % survival rate of treated seeds or explants. This balance ensures a high enough mutation load without excessive lethality, which would reduce the population size for selection. In vitro random mutagenesis relies on the application of physical and chemical mutagens to increase the frequency of mutations thus accelerating the selection of varieties with important agronomic traits. Mutation breeding consists of three main elements to develop a new trait: mutation induction, selection of desirable mutants through phenotypic screening and genetic characterization using molecular markers. Mutation breeding involves three key steps: mutation induction, phenotypic selection and genetic characterization them using molecular markers (e.g., DNA markers, SNPs) to understand the genetic basis of the observed traits. The physical mutagens are successful; breeders are inclined breeders are given increasingly inclined to use novel genome editing tools like CRISPR/Cas9 gene editing technology to modify plants. The limitations of random mutagenesis, breeders are increasingly adopting novel genome editing technologies. Tools like Zinc Finger Nucleases (ZFNs), Transcription Activator-Like Effector Nucleases (TALENs), RNA interference (RNAi) and especially CRISPR/Cas systems offer several advantages. CRISPR/Cas9 offers precise genome editing capabilities. It enables targeted modifications that enhance desirable traits and address critical challenges in fruit production. This review provides mutagenesis techniques and their applications, emphasizing their importance in developing improved and sustainable fruit cultivars to meet the demands of a growing global population.